Diversity of fungi isolated from the carapace of the European pond turtle (Emys orbicularis, L. 1758) in South Banat, Serbia - Stupar Miloš Č.; Savković Željko D.; Ljaljević-Grbić Milica V.; Krizmanić Imre I. (Archives of Biological Sciences, 2025)
This study aimed to isolate and identify a fungal community on the carapace of the European pond turtle (Emys orbicularis) and to discuss their potential role as constituents of the turtle mycobiome. The study was conducted during the summer of 2020 within the special nature reserve Deliblato Sands (Deliblatska Peščara), situated in northern Serbia. We used a direct microscopy technique along with culture-based methods and molecular barcoding of the internal transcribed spacer (ITS) region. A plethora of fungal spores were documented as constituents of the biofilm present on the carapace surfaces. A total of 12 fungal isolates from the E. orbicularis carapace were identified, belonging to Alternaria, Aureobasidium, Cladosporium, Curvularia, Didymella, Microsphaeropsis, Pseudopithomyces, Naganishia, Rhodotorula, and Mucor genera. Ecological analyses showed that the majority of documented fungal species originated from terrestrial and aquatic environments, and many could be regarded as potential chelonian pathogens. The study presents pioneering research on fungal dwellers of E. orbicularis in Serbia.